Republic of Poland : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the economic development of Poland after the recession is discussed. The importance of maintaining macroeconomic policies and advancing growth-enhancing structural reforms are explained. Increase in labor participation and a reduction in product market rigidities are key to increase potential growth. Improvements of the balance of payments compilation system has been encouraged by the authorities. To strengthen the financial sector, increase the independence of financial supervision authority, develop a framework for coordinating policy responses to systemic risks, and strengthen the bank resolution framework are also encouraged.